ATIVIDADE ANTI-Candida de Vismia guianensis (Aubl.) Chosy: AVALIAÇÃO in vitro, in vivo e in silico. - MOTTA, Elizangela Araújo Pestana (2020)
Vismia guianensis (Aubl.) Chosy, a typical plant species from the Amazon region, is popularly used to treat skin infections, as healing and purgative. We investigated the anti-Candida effect of hydroethanolic extract from the leaves of V. guianensis (EHVG) in vitro, in vivo, and in silico. The leaves were macerated in alcohol (70%), for 7 days, followed by evaporation and lyophilization to obtain the EHVG. The EHVG was submitted to phytochemical screening and chromatographic characterization by HPLC-UV and FIA-ESI-IT-MSn. The EHVG cytotoxicity was evaluated by neutral red, MTT, and by determination of hemolytic activity. The antifungal activity in vitro was assessed by the minimum inhibitory concentration (MIC) and minimum fungicide (CFM) using standard strains of Candida albicans, C. glabrata, and clinical isolates of C. albicans. It was also evaluated in vitro the effects of EHVG on the virulence factors such as fungic adhesion, young and mature biofilms, and fungal growth kinetics. In another group of experiments, we determined the effect of EHVG on the proteolytic enzymes using two C. albicans strains, one sensitive (Ca(S)Flu), and the other resistant (Ca(R)Flu) to Fluconazole. The synergistic effect of EHVG with Amphotericin B or Fluconazole was also determined. The in vivo evaluation was performed in Swiss female mice, immunosuppressed with cyclophosphamide, 48 hours before the lethal infection by C. albicans (3x108). Groups treated with EHVG (5mg/kg), at the time of infection, or 6 hours later, were compared to the untreated control group. The in silico analysis was performed by molecular docking and molecular dynamics simulations, using the enzyme CaCYP51 from C. albicans as the target and four compounds identified in the EHVG. Posaconazole was the positive control in this assay. According to the phytochemical screening, EHVG is rich in catechins, saponins, anthocyanins, anthocyanidins, benzoquinones, and flavonoids. After the chemical characterization of EHVG, it was possible to identify as the main compounds: vismiona D, anthraquinone F, kaempferol, quercetin, and ellagic acid. EHVG presented low cytotoxicity at the various concentrations and efficiently inhibited the growth of both planktonic forms and biofilms formation. The EHVG presented a synergistic effect when associated either to Fluconazole or Amphoterin B and showed an anti-Candida effect even in the Ca(R)Flu strain. Animals treated with EHVG, always, presented better survival and longer life expectancy, with similar efficacy to standard drugs. The four evaluated compounds showed high affinity for the enzyme CaCYP51 after in silico analysis. However, Vismiona D presented better results, even superior to Posaconazole. We conclude that EHVG exhibits anti- Candida activity, in vitro as in vivo, confirming the in silico assays, probably because it can inhibit the various fungus virulence mechanisms, even in the Fluconazole resistant strain. It is possible to suggest that the anti-Candida action may be due to the combination of at least four chemical compounds present in the extract, but vismione D, seems to be the most effective. Based on this, it is reasonable to propose Vismia guianensis as an essential target for bioprospecting new drugs for the Candida infections treatment.